Psychometric validation of concerning behavior scale in Iranian children and young people with autism spectrum disorder - Mohammadi, Kourosh; Samavi, Abdolvahab; Mehdiabadi, Fatemeh Zare; Samavi, Seyed AbdolHadi (Frontiers in Psychiatry, 2023)
Assessment of Concerning Behavior (ACB) was introduced by Tarver et al (2021) to evaluate mental health and problematic/risky behaviors in children and young people with autism spectrum disorder (ASD). This study examined the psychometric validation of the Assessment of Concerning Behavior (ACB) in an Iranian sample of parents of children and young people with ASD. Confirmatory factor analysis was conducted to examine the structure of ACB in a sample of 303 parents. The data supported the two factor structure, all factor loadings were significant and scale structure was confirmed similar to the original scale. The results supported the two-factor structure for ACB that included internalizing and externalizing problems scales. The two factors of ACB are positively correlated with Aberrant Behavior Checklist scores which showed that the validity of two factors is satisfactory. The reliability of the two subscales was reasonable as well. The study suggests that the ACB could be an operational tool to assess the mental health and problematic/risky behaviors in Iranian children and young people with ASD.